2021
DOI: 10.3390/e24010068
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Algorithm to Predict Acidemia Using Electronic Fetal Monitoring Recording Parameters

Abstract: Background: Electronic fetal monitoring (EFM) is the universal method for the surveillance of fetal well-being in intrapartum. Our objective was to predict acidemia from fetal heart signal features using machine learning algorithms. Methods: A case–control 1:2 study was carried out compromising 378 infants, born in the Miguel Servet University Hospital, Spain. Neonatal acidemia was defined as pH < 7.10. Using EFM recording logistic regression, random forest and neural networks models were built to predict a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…From the experiment results, they concluded that machine learning models perform better as compared to traditional ones. The RF and NN produced quite efficient results with AUC values of 0.865 and 0.857 for validation data (confidence interval: CI 95%) as compared to the LRM (AUC value = 0.840 and CI = 95%) [199].…”
Section: Classification and Performance Evaluationmentioning
confidence: 97%
“…From the experiment results, they concluded that machine learning models perform better as compared to traditional ones. The RF and NN produced quite efficient results with AUC values of 0.865 and 0.857 for validation data (confidence interval: CI 95%) as compared to the LRM (AUC value = 0.840 and CI = 95%) [199].…”
Section: Classification and Performance Evaluationmentioning
confidence: 97%
“…Unlike previous studies that relied on manual methods of EFM record measurements, which are time-consuming and less practical in a clinical setting, our study utilized a computerized method, enabling us to move towards realtime analysis of fetal heart rate. The exploration of automated EFM analysis has also gained attention in recent research, with studies investigating real-time algorithmic analysis [28,29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A study conducted in 2021 [28] compared different models and highlighted the importance of AUC in predicting fetal acidemia. While machine learning methods employed in these studies are effective at identifying relationships that may be hidden from human reasoning, they often lack traceability and intuitive interpretation [30].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Machine learning algorithms possess the ability to handle vast amounts of data derived from the FHR signal and identify patterns that may not be easily discernible through traditional methods, enabling the analysis of complex relationships [15]. This is particularly crucial in predicting acidemia, as subtle changes in the FHR signal can indicate the onset of fetal distress [16,17].…”
Section: Introductionmentioning
confidence: 99%